2014
DOI: 10.1089/mdr.2013.0192
|View full text |Cite
|
Sign up to set email alerts
|

Macrolide, Lincosamide, and Streptogramin B Resistance in Lipophilic Corynebacteria Inhabiting Healthy Human Skin

Abstract: Corynebacteria exist as part of human skin microbiota. However, under some circumstances, they can cause opportunistic infections. The subject of the study was to examine the macrolide-lincosamide-streptogramin B (MLSB) antibiotic resistance in 99 lipophilic strains of Corynebacterium genus isolated from the skin of healthy men. Over 70% of the tested strains were resistant to erythromycin and clindamycin. All of which demonstrated a constitutive type of MLSB resistance mechanism. In all strains, there were be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
4
12
0
1
Order By: Relevance
“…The constitutive MLS B resistance mechanism was also demonstrated in 13 resistant strains isolated from healthy human skin (72%). These strains were harboring only the erm(X) gene what has confirmed our previous observations (Szemraj et al, 2014). It draws the attention that we detected for the first time a large number of clinical isolates of Corynebac te rium spp.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The constitutive MLS B resistance mechanism was also demonstrated in 13 resistant strains isolated from healthy human skin (72%). These strains were harboring only the erm(X) gene what has confirmed our previous observations (Szemraj et al, 2014). It draws the attention that we detected for the first time a large number of clinical isolates of Corynebac te rium spp.…”
supporting
confidence: 91%
“…is noticeable especially in clinical multidrug-resistant isolates (Otsuka et al, 2006;Ortiz-Perez et al, 2010). Nevertheless, in a manuscript published in Microbial Drug Resistance in 2014 (Szemraj et al, 2014), we have shown that this resistance may also occur in the skin microbiota e.g. C. tuberculostearicum or C. jeikeium.…”
mentioning
confidence: 83%
“…As found in this study, strains of C. tuberculostearicum are often multiresistant, demonstrating the macrolide-lincosamidestreptogramin B (MLSB) mechanism conferred by the ermX gene (23,24). While data are limited, antimicrobial susceptibility by nonstandardized disk diffusion has been performed on isolates of C. kroppenstedtii, reporting broad susceptibility to most classes of antimicrobials (9,11).…”
Section: Discussionmentioning
confidence: 62%
“…This inflammatory reaction can be rapid; in our series, the development of granulomata was seen as early as a week from the start of clinical symptoms. In this environment, adequate tissue concentrations for bactericidal activity may be achieved by agents that are highly lipophilic and have a high volume of distribution, which include rifampin, clarithromycin, trimethoprim-sulfamethoxazole, and clindamycin (24,25). In contrast, ␤-lactams and fluoroquinolones have low lipid solubility and therefore are expected to be less effective.…”
Section: Discussionmentioning
confidence: 99%
“…mph(C) has also been identified in corynebacteria from healthy human skin (Szemraj et al 2014) and, interestingly, in Stenotrophomonas maltophilia .…”
Section: Phosphotransferasesmentioning
confidence: 96%